Outpatient visit among elderly in Indonesia - Haerawati Idris; Nurafni Nurafni (Intelektual Pustaka Media Utama, 2021)
Population aging has become an important issue mostly discussed in many countries in the world. The proportion of the older population is getting better in both developed and developing countries. Elderly tend to need more health care as they are more susceptible to chronic diseases. The purpose of this study was to determine the factors affecting outpatient visit among elderly in Indonesia. This study employed a cross-sectional study design with a sample of ≥60-year-old individual with a total sample of 5,325 elderly. The data used to be analyzed were from the Indonesian Family Life Survey 2014 representing 83% of the population in Indonesia. The theory used was Andersen health service utilization model. In analyzing the data, bivariate analysis were used, with Chi-square and multivariate test using multiple logistic regression test prediction model. Elderly who utilize health service for outpatient was 18.6%. Variables that have significant relationships with outpatient utilization on elderly were female, high education, formal job, Java and Bali, urban, health insurance ownership, economic status, the perception of ill, smoking habit, history of chronic disease, fat, and obesity. Predictor for the most dominant outpatient utilization is influenced by chronic disesase after controlled by other variables. Chronic disesase greatly affect the elderly in utilizing health services for outpatient. To overcome this, the government is expected to provide policies on health facilities to better emphasize promotive and preventive efforts among the elderly.